Selection of the Best Lean Construction Techniques for the Execution Stage - Satriyo Agus Adi Prastyo; I Putu Artama Wiguna (Newinera Publisher, 2026)
This study aims to identify and prioritize critical success factors and lean construction techniques that influence lean implementation during the execution stage of construction projects in Indonesia. A quantitative research approach was employed using expert judgment collected through a structured questionnaire. The Relative Importance Index was applied to rank critical success factors and assess the importance of selected lean construction techniques, while the Analytic Hierarchy Process was used to determine priority weights through pairwise comparisons. The results indicate that top management, financial management, task execution based on scope of work, and improvement tools are the most influential factors supporting successful lean execution. The analysis also shows that Just In Time, Last Planner System, Daily Huddle Meeting, and Building Information Modeling are all considered very important techniques during the execution stage. Further prioritization reveals that Daily Huddle Meeting has the highest priority, followed by Just In Time, while Building Information Modeling and Last Planner System function as supporting techniques. The findings highlight that effective lean execution is driven primarily by managerial commitment and daily coordination practices rather than technical tools alone. This study provides practical guidance for construction practitioners in selecting appropriate lean strategies to improve execution performance and reduce waste on site.